FEATURES OF THE ADMINISTRATIVE AND LEGAL STATUS OF THE TEAM OF THE AIR TRANSPORT OF UKRAINE - Дараганова, Н. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
In the article are explored some questions in relation to the features of administrative and legal status o fthe commander of the aircraft of Ukraine and certified, that the commander of the aircraft is a person,which by virtue of his responsibility is provided for safe realization of flight with the specialimperious rights and plenary powers in relation to all persons, which are on the side of this aircraft.